The Influence of Operational Constraints of Culinary Tourism Centers on The Sustainability of UMKM and Socio-Economic Impacts - Rabbani, Jalaludin; Saputra, Aan; Wahjono, Sentot Imam (Golden Ratio of Data in Summary, 2025)
This study aims to analyze how operational constraints in the Culinary Tourism Center (SWK) affect the sustainability of micro, small, and medium enterprises (MSMEs), and their impact on the socio-economic aspects of the surrounding community. Through an organizational behavior approach, this study examines the influence of leadership, work culture, and conflict management in managing SWK. The results of the study indicate that limited infrastructure, lack of human resource training, and ineffective operational management have led to a decrease in the competitiveness of MSMEs and have a negative impact on the local economic cycle. This study recommends improving leadership strategies, organizational communication, and managerial training as steps to overcome these constraints and support the desires of MSMEs in the SWK environment.